Genetic variation in the renin-angiotensin system and athletic performance - Alvarez, R.; Terrados, N.; Ortolano, R.; Iglesias Cubero, G.; Reguero, J. R.; Batalla, A.; Cortina, A.; Fernandez-Garcia, B.; Rodriguez, C.; Braga, S.; Alvarez, V.; Coto, E. (European Journal of Applied Physiology, 2000)
The D allele at the angiotensin-I-converting enzyme (ACE)-insertion/deletion polymorphism has been associated with an increased risk of developing several pathological processes, such as coronary heart disease and ventricular hypertrophy. Individuals with the DD genotype show a significantly increased left-ventricular mass in response to physical training, compared to the II genotype (which would be associated with the lowest plasma ACE levels) and the ID genotype. The II genotype has been linked to a greater anabolic response. In accordance with a role for ACE in the response to rigorous physical training, a higher frequency of the I allele has been reported to exist among elite rowers and high-altitude mountaineers. Sixty elite (professional) athletes (25 cyclists, 20 long-distance runners, and 15 handball players), and 400 healthy controls were genotyped for the DNA polymorphisms of the ACE, angiotensinogen (Ang) and angiotensin receptor type 1 (AT1) genes. Plasma ACE levels showed a strong correlation with the I/D genotype in our population. The I-allele occurred at a significantly higher frequency in athletes compared to controls (P=0.0009). Gene and genotype frequencies for the Ang and AT1 polymorphisms did not differ between athletes and controls. Since the frequency of the ACE I allele was significantly increased among our elite athletes, we conclude that the ACE polymorphism represents a genetic factor that contributes to the development of an elite athlete.